2002
DOI: 10.1097/00006454-200206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Variations in central venous catheter-related infection risks among Canadian neonatal intensive care units

Abstract: CVC use increased the risk of nosocomial blood stream infection. The risk of nosocomial blood stream infection in percutaneous and Broviac catheters was 70 to 80% higher than in umbilical venous catheters. There was significant variation in CVC-related infection risks among Canadian NICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
4
7

Year Published

2005
2005
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 24 publications
9
89
4
7
Order By: Relevance
“…The central venous (Silastic) catheters were inserted by a member of medical staff under an aseptic technique. One unit of heparin Potentially relevant RCTs identified and screened for retrieval (n=35) RCTs excluded without indwelling catheters or central venous line Studies were excluded because did not use an antibiotic and used other lock or flush solution (19) and included adult population (1) RCTs retrieved for more detailed evaluation (n=23)…”
Section: Description Of Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The central venous (Silastic) catheters were inserted by a member of medical staff under an aseptic technique. One unit of heparin Potentially relevant RCTs identified and screened for retrieval (n=35) RCTs excluded without indwelling catheters or central venous line Studies were excluded because did not use an antibiotic and used other lock or flush solution (19) and included adult population (1) RCTs retrieved for more detailed evaluation (n=23)…”
Section: Description Of Studiesmentioning
confidence: 99%
“…Central venous lines (CVLs) are routinely used for monitoring and the administration of total parenteral nutrition (TPN) and medications in neonatal intensive care units (NICUs) 1 A prospective cohort study on 19 000 infants admitted to NICUs, CVLs were placed in 22.5% of patients and were associated with a significant risk of systemic bacterial infection. 1 One study showed the rate of CVL-associated bacteremia to be 13 per 1000 percutaneous catheter days compared to 3 per 1000 days in infants without a CVL.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations